The Wild Garden of Modernism: Intermedial Woolf - Legarreta Mentxaka, Aintzane (2023)
This essay looks at Virginia Woolf’s use of nature. She used gardens to rethink human values and human perception. In descriptions of nature, she showed how human-centred views of the world, and our sense of the passage of time, are inadequate. Her stylistic experimentation included intermediality: the mixture of two art forms. Looking at the short story “Kew Gardens” (1919) and the novel The Years (1937), this essay considers how she adapted techniques from film and painting. In this way, she cultivated a modernist mixture of sophistication, depth, playfulness, and surprise.